Predictive value of admission red cell distribution width-to-platelet ratio for 30-day death in patients with spontaneous intracerebral hemorrhage: an analysis of the MIMIC database - Liang, Hanbai; Liu, Ping; Guo, Lei; Feng, Jie; Yin, Cheng; Zhao, Dongdong; Chen, Longyi (Frontiers in Neurology, 2023)
Aim Prognostic assessment plays an important role in the effective management of patients with spontaneous intracerebral hemorrhage (ICH). The study aimed to investigate whether elevated red cell distribution width-to-platelet ratio (RPR) at admission was related to 30-day death in patients with spontaneous intracerebral hemorrhage (ICH). Methods This retrospective cohort study included 2,823 adult patients with ICH from the Multiparameter Intelligent Monitoring in Intensive Care (MIMIC) III and IV databases between 2001 and 2019. The Cox proportional hazard model was utilized to evaluate the relationship between RPR levels and 30-day death risk. The area under receiver-operating characteristic curve (AUC) was used to assess the predictive ability of RPR for 30-day death in patients with ICH. Results At the end of the 30-day follow-up, 799 (28.30%) patients died, and the median RPR level was 0.066 (0.053, 0.087). After adjusting for confounders, the tertile 3 of RPR levels [hazard ratio (HR) = 1.37, 95% confidence interval (CI): 1.15–1.64] were associated with a higher risk of 30-day death in patients with ICH compared with tertile 1. In the stratified analyses, elevated RPR levels were found to be associated with an increased risk of 30-day death in patients aged <65 years (HR = 1.77, 95%CI: 1.29–2.43), aged ≥65 years (HR = 1.30, 95%CI: 1.05–1.61), with Glasgow Coma Score (GCS) <14 (HR = 1.65, 95%CI: 1.27–2.14), with Charlson comorbidity index (CCI) ≥4 (HR = 1.45, 95%CI: 1.17–1.80), with (HR = 1.66, 95%CI: 1.13–2.43) or without sepsis (HR = 1.32, 95%CI: 1.08–1.61), and female patients (HR = 1.75, 95%CI: 1.35–2.26) but not in male patients (P = 0.139) and patients with GCS ≥14 (P = 0.058) or CCI <4 (P = 0.188). The AUC for RPR to predict 30-day death in patients with ICH was 0.795 (95%CI: 0.763–0.828) in the testing set, indicating a good predictive ability. Conclusion Elevated RPR levels were correlated with an increased risk of 30-day death in patients with ICH, and RPP levels showed good predictive ability for 30-day death.